Enhanced XUV harmonics generation from diatomic gases using two orthogonally polarized laser fields - Ganjaboy S. Boltaev (Nature Portfolio, 2021)
Abstract Enhanced high repetition rate coherent extreme ultraviolet (XUV) harmonics represent efficient probe of electron dynamics in atoms, molecules and solids. In this work, we used orthogonally-polarized two-color laser field to generate strong even and odd high order harmonics from molecular gas targets. The dynamics of odd and even harmonics from O2, and N2 gases were investigated by employing single- and two-color laser fields using the fundamental radiation and second harmonic of 1030 nm, 37 fs, 50 kHz pulses. The relative efficiencies of harmonics were analyzed as a function of the thickness of the barium borate crystal used for second harmonic generation. Defocusing-assisted phase matching conditions were achieved in N2 gas for different groups of XUV harmonics.